Asthma Current Perspectives on Phenotypes, Endotypes, and Treatable Traits - Rovina, Nikoletta (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Asthma is a common complex and heterogeneous respiratory disease with an increasing prevalence in developed countries. Asthma is a disease consisting of different phenotypes that are driven by different mechanistic pathways (endotypes). The recognition of these phenotypes and endotypes is central to asthma management entailing prognostic and therapeutic implications. It is acknowledged that despite optimal treatment, many patients are poorly controlled, highlighting the need for phenotype-guided treatments. In this context, the emergence of novel therapies (monoclonal antibody therapy, bronchial thermoplasty) is paving the way for personalized asthma therapy. A better understanding of disease pathogenesis may enable the identification of biomarkers, mediators, novel therapeutic targets, and treatable traits. Further molecular phenotyping or endotyping of asthma will be necessary to tailor new therapeutic strategies. The present Special Issue on Asthma aims to provide the current knowledge on phenotypes and endotypes in appreciating and managing the heterogeneous condition that is asthma.